2020
DOI: 10.1088/1757-899x/959/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of chemistry laboratory basic skills using performance scoring rubrics at the chemistry teacher training

Abstract: This student self-assessment of chemistry laboratory basic skill performances is intended to overcome the heavy time-consuming and very intensive involvement of lecturer as the only performance assessor, promote and accelerate the skill improvement based on learner self-performance assessment. The study involved 26 students undertaking Basic Chemistry subject at Chemistry Education Department of Universitas Pendidikan Ganesha in Bali. The self-assessment applied the scoring rubric developed by Sudria and Sya’b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The former two skills seem to be not only relevant to inquiry experiments exclusively but also to cook-book experimentation. For example, Sudria and colleagues included observing in a set of practical laboratory skills [78].…”
Section: Discussion and Limitations Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The former two skills seem to be not only relevant to inquiry experiments exclusively but also to cook-book experimentation. For example, Sudria and colleagues included observing in a set of practical laboratory skills [78].…”
Section: Discussion and Limitations Of The Studymentioning
confidence: 99%
“…For example, Atzert and colleagues demonstrated that self-concept of ability can be measured regarding science experimentation [77]. Sudria and colleagues [78] compared self-assessment and objective assessments of preservice chemistry teacher students' practical skills in a chemistry labora-tory. Their findings suggest that both students' self-assessed skills at the beginning and during the course correlate with objective assessment of their performance by the lecturer.…”
Section: Self-concept Of Ability and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, the disadvantage of using such skills–lab approaches as a method of evaluating student skill development is often the time-consuming nature of evaluating individual student performances within a short period of time. To maintain the ability to monitor student skill development, but with a lower time commitment for the course instructor, a recent study described the use of student self-assessments for basic laboratory skills developed in a general chemistry course . To evaluate the development of more than one chemical laboratory skill, significant support from instructors and teaching assistants (TAs) is required.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the ability to monitor student skill development, but with a lower time commitment for the course instructor, a recent study described the use of student self-assessments for basic laboratory skills developed in a general chemistry course. 22 To evaluate the development of more than one chemical laboratory skill, significant support from instructors and teaching assistants (TAs) is required. Naturally, the reliance on a large number of teaching assistants has the potential to introduce grading inconsistencies into the evaluation method, especially if teaching assistants themselves are not properly trained to recognize the subtleties of performing the selected skills.…”
Section: ■ Introductionmentioning
confidence: 99%